Relasi antara Tuhan dan Manusia Menurut Pandangan IbrÄhÄ«m al-KurÄnÄ« - Mubarok, Frenky (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
This article describes the concepts of relationship of God and man from theological point of view along with Sufism. It focuses on Ibr?h?m al-Kur?n??s view on the issue. This article confirms that al-Kur?n? attempts to reconcile theological views of Ash?ar?yah and the divine worldviews of the Sufis, especially that of Ibn ?Arab??s philosophical Sufism. Al-Kur?n? argues that there has been interconnectedness between common concepts expressed by the Sufis such as wa?dat al-wuj?d and tajall? and the concept of al-kasb promulgated by Ash?ar?yah. The author finds that the concepts of itti??d and ?ul?l are not two mystical concepts that explain the relationship of God and man, rather these two concepts are a mere psychological condition sensed and experienced by the Sufis who try to enter the realm of ma?rifat. Al-K?r?n? also argues that the relation of God and man can be explained through the concept of tajall?. He sees that this concept is compatible with Ash?ar?yah?s concept of al-kasb. Al-K?r?n? adds that causality is not an undoubtedly exact matter. It means that the causality does not discord against the notion of wa?dat al-wuj?d.